Bibliografia sobre pastoral urbana - Centro Ecumênico de Evangelização, Capacitação e Assessoria, CECA - (2013)
This is a "Bibliography on Urban ministry" compiled by advisors from the Centro Ecumênico de Evangelização, Capacitação e Assessoria (CECA).